I'JAZ QUR'AN MENURUT PANDANGAN ULAMA MUKTAZILAH - Suci Shalwa Fauzi; Era Asria Harahap; Rika Amalia Ritonga; Harunalrasyid (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research aims to explore the munasabah of the Qur'an in the tafsir al- Kashshaf as one of the phenomenal Mu'tazilah tafsir. With this exploration, the research also aims to prove that there is a shift in the meaning of i'jaz al- Qur'an from the meaning of surah which means Allah turned human ability to make something like the Qur'an to the meaning of nazm which means i'jazan of al-Qur'an lies in the order of expression. There is a close relationship between the nazm of the Qur'an and the munasabah of the Qur'an. The research found that there is a munasabah of the Qur'an in the interpretation of al-Kashshaf. From the five letters studied, namely al-Fatihah, al-Baqarah, Ali 'Imran, al-Nisa, and al-Maidah, various variations and patterns of munasabah of the Qur'an were found. There are four types of munasabah in the Qur'an, namely munasabah word for word in one verse, munasabah between verses and the following verse, munasabah between verses in one letter, and munasabah between verses in different letters. Meanwhile, the patterns of recitation of the Qur'an that were found consisted of five patterns, namely interpretation (al-tafsir), insertion (al-i'tiraf}), comparison (al-tanzir), resistance (al-mud}adha), and diversion. (iltifate). With these findings, the research also confirms that Zamakhsyari in his interpretation of al-Kashshaf does not follow the concept of i'jaz al-Qur'an with surahs that are identical to the views of his Mu'tazilah school of thought which were echoed by figures such as Nazam, Jahiz, Rummani, and also Sharif Murtad}a. Zamakhsyari prefers the concept of nazm which was initiated by Jurjani and also Baqillani who belongs to the Ash'ariyah school of thought. This research is a qualitative research that uses the interpretation of Zamakhsyari in the tafsir al-Kashshaf as research data. Meanwhile, the data analysis technique used is Content Analysis of the interpretation of al-Kashshaf. to obtain a classification of the munasabah content of the Qur'an in it.